1995
DOI: 10.1016/0014-2999(95)00498-x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral ischemia in gerbils: effects of acute and chronic treatment with adenosine A2A receptor agonist and antagonist

Abstract: Despite significant progress in understanding of the potential of adenosine A 1 receptor-based therapies in treatment of cerebral ischemia and stroke, very little is known about the effect of selective stimulation of adenosine A 2A receptors on the outcome of a cerebrovascular arrest. In view of a major role played by adenosine A 2 receptors in the regulation of cerebral blood flow, we have investigated the effect of both acute and chronic administration of the selective adenosine receptor agonist 2-[(2-aminoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(70 citation statements)
references
References 30 publications
6
64
0
Order By: Relevance
“…But the first report by Phillis' group that a non-selective A 2A R antagonist (CGS 15943) attenuated cerebral ischemic injury [225], in contrast to A 1 R antagonists [226], appeared as a serendipitous observation. Similar observations were made by von Lubitz in a similar gerbil model of brain ischemia [227]. However, this concept of A 2A R blockade as a neuroprotective strategy was difficult to understand at the time and consequently was not widely accepted until the group of Ongini and the group of Chen demonstrated that both the pharmacological blockade of A 2A Rs with a selective antagonist (SCH 582610) [228] as well as the genetic inactivation of A 2A Rs (using A 2A R knockout mice) [229] conferred a robust neuroprotection in animal models of focal ischemia.…”
Section: A 2a Receptor Blockade Confers Robust Neuroprotectionsupporting
confidence: 88%
“…But the first report by Phillis' group that a non-selective A 2A R antagonist (CGS 15943) attenuated cerebral ischemic injury [225], in contrast to A 1 R antagonists [226], appeared as a serendipitous observation. Similar observations were made by von Lubitz in a similar gerbil model of brain ischemia [227]. However, this concept of A 2A R blockade as a neuroprotective strategy was difficult to understand at the time and consequently was not widely accepted until the group of Ongini and the group of Chen demonstrated that both the pharmacological blockade of A 2A Rs with a selective antagonist (SCH 582610) [228] as well as the genetic inactivation of A 2A Rs (using A 2A R knockout mice) [229] conferred a robust neuroprotection in animal models of focal ischemia.…”
Section: A 2a Receptor Blockade Confers Robust Neuroprotectionsupporting
confidence: 88%
“…The striking pattern of the dependence of physiological and therapeutic effects of adenosine receptor stimulation on the dose (Ceruti et al, 1996) and/or duration of exposure to the stimulating agent (present study; Von Lubitz et al, 1994aLubitz et al, , 1995b may be related to desensitiza-tion of receptor-coupled G proteins. Chronic exposure of rat adipocytes to a selective adenosine A: agonist R-phenylisopropyladenosine (R-PIA) results in a profound loss of immunoreactivity for G proteins, particularly G iα1 and G iα3 , both in vitro and in vivo (Longabaugh et al, 1989).…”
Section: Discussionmentioning
confidence: 51%
“…It is likely therefore, that the release of ATP and adenosine under ischemic conditions is mechanistically and temporally separated [49] , suggesting that the initial elevations in ATP can activate neurodegenerative mechanisms that may be followed, after conversion of ATP to adenosine by neuroprotective and neurodegenerative roles for the purines. However, this appears to be strongly dependent upon CNS region, animal model and the type of insult, and requires more investigation to elucidate these complex mechanisms [80,[84][85][86][87][88][89][90][91][92][93][94][95][96] .…”
Section: Purinergic Receptorsmentioning
confidence: 99%